From "a Fair Game" to "a Form of Covert Research": Research Ethics Committee Members' Differing Notions of Consent and Potential Risk to Participants Within Social Media Research. (April 2018) - Hibbin, R. A.; Samuel, G.; Derrick, G. E.
Social media (SM) research presents new challenges for research ethics committees (RECs) who must balance familiar ethical principles with new notions of public availability. This article qualitatively examines how U.K. REC members view this balance in terms of risk and consent. While it found significant variance overall, there were discernible experience-based trends. REC members with less experience of reviewing SM held inflexible notions of consent and risk that could be categorized as either relying on traditional notions of requiring direct consent, or viewing publicly available data as "fair game." More experienced REC members took a more nuanced approach to data use and consent. We conclude that the more nuanced approach should be best practice during ethical review of SM research.